Body weight, oestrous and ovarian activity in local Burundian ewes and goats after parturition in the dry season - Mbayahaga, J.; Mandiki, S.N.M.; Bister, J.L.; Paquay, R. (Elsevier, 1998)
To compare body weight losses and post-partum anoestrus, twelve local Burundian ewes and twelve goats which had lambed or kidded at the middle of the dry season were followed from parturition until eight months. Each dam was weighed every month and bled three times a week to assess the ovarian activity resumption by plasma progesterone (P4) profiles. For the two species, the body weight decreased significantly (p